Particle impact prediction of an archimedes screw runner blade for micro hydro turbine - Nurul Suraya, Azahari (2013)
Energy is one of the important sources in the world and important for developing countries. In rural and remote areas, transmission and distribution of energy generated from fossil fuels can be difficult and expensive and producing renewable energy such as water turbine can locally offer a viable alternative. The subject study is conducted to investigate the flow behaviour of water inside the turbine and predict the impact of particle towards blade surface. For this reasons, computational fluid dynamics (CFD) methods are used. The three-dimensional flow of fluid is numerically analysed using the Navier-Stokes equation with standard k-ε turbulence model by applying some boundaries condition such as steady state flow condition, isentropic flow and isothermal temperature. The numerical results such as velocity streamlines, flow pattern and pressure contour for flow of water entering the blade are compared with the experimental results which obtained by other researches. This study shows that the prediction of particle impact occurs mostly on the entering surface blade and along the leading edge of the screw runner. Any modification on the design of the screw runner blade can be analyse for further study.